The World Bank Annual Report 2006 - World Bank (World Bank Annual Report, 2006)
The World Bank Annual Report 2006 is the one place where you will find: a summary of the World Bank's major initiatives and activities this year; regional reports with lending to each region by theme and sector; the year's lending and advisory activities; a description of all new projects approved this year; the complete financial statements of the World Bank; and World Bank organizational information, including a list of all Country Offices. You'll find numerous references to Web sites where you can find in-depth information on every topic in the Annual Report